Increasing sexual misconduct: Going beyond victim blaming - Nilanjana Ghosh; Purushottam Giri (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
India is a country known for its heritage. Man protecting woman has been long considered a virtue rather than good conduct in our country. Just like good clinical practices in research there are few basic tenets on which every society stands and socio-cultural systems are built up.